Multi-agent and complex systems - Bai, Quan; Ren, Fenghui; Fujita, Katsuhide; Zhang, Minjie (Computer scientist); Ito, Takayuki, 1972- (Studies in computational intelligence ;, 2016)
This book provides a description of advanced multi-agent and artificial intelligence technologies for the modeling and simulation of complex systems, as well as an overview of the latest scientific efforts in this field. A complex system features a large number of interacting components, whose aggregate activities are nonlinear and self-organized. A multi-agent system is a group or society of agents which interact with others cooperatively and/or competitively in order to reach their individual or common goals. Multi-agent systems are suitable for modeling and simulation of complex systems, which is difficult to accomplish using traditional computational approaches.